2007
DOI: 10.1017/s1368980007668724
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity and body composition of black township adolescents residing in the North West Province, South Africa

Abstract: Objective: It is known that stunting and obesity affect a large proportion of children in the world, and these can be affected by the physical activity levels of the children. In the present study, we evaluated the association between physical activity, physical development and body composition in black adolescent children. Design: Cross-sectional study. Setting: Black township schools in the North West Province, South Africa. Methods: Three-hundred and thirteen grade 8 children were included in the Physical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In line with previous findings [18], [43], stunted children (whether or not overweight) were found to be less active than their non-stunted (whether or not overweight) counterparts. This reduced level of physical activity may expose stunted children to a higher risk of in a context of nutrition transition [44].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous findings [18], [43], stunted children (whether or not overweight) were found to be less active than their non-stunted (whether or not overweight) counterparts. This reduced level of physical activity may expose stunted children to a higher risk of in a context of nutrition transition [44].…”
Section: Discussionsupporting
confidence: 92%
“…In one of these studies, “obesity prevalence varied from 1.1% (Dutch and Danish girls) to 10.7% (Portuguese boys) and from 0.3% (Dutch girls) to 6.2% (Portuguese boys) respectively” [61]. Reasons for the different patterns in LMICs and High Income countries could include cultural beliefs about body image [62], and higher levels of physical activity including harder chores and manual labour among adolescent boys in LMICs than girls [62, 63]. Given such prevalence of unhealthy weights but no significant associations with potential risk factors, our findings seem to suggest that other factors not captured by the questions in the survey may be related to the weight status of these adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most compelling findings of our study is its consistency with the international phenomenon of low PA in adolescents [22,23]. Up until now, most of the studies on habitual PA in South Africa were done using questionnaires [4,24]. However, pedometers [14] and accelerometry [15] have been used to assess PA in rural black female South Africans as well as 8–12 year old South African children from disadvantaged schools [25].…”
Section: Discussionmentioning
confidence: 69%
“…With reference to South African adolescents from the Tlokwe Municipality of the North West Province, it is possible that walking to school (Non Exercise Activity Thermogenesis–NEAT transport domain) [29] or school related physical education/scheduled sport is the reason behind higher weekday MVPA. Conversely, in 2008, Mamabolo and colleagues revealed that ±14½ year old township adolescents residing in the North West Province of South Africa were more active on weekends than on weekdays [24]. This disparity is likely due to the fact that Mamabolo and colleagues used questionnaires and not objective means to asses PA.…”
Section: Discussionmentioning
confidence: 99%